2017
DOI: 10.1007/s00127-017-1383-z
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance attendances resulting from self-harm after release from prison: a prospective data linkage study

Abstract: Ambulance attendances resulting from self-harm following release from prison are common and represent an opportunity for tertiary intervention for self-harm. The high prevalence of such attendances, in conjunction with the strong association with prior psychiatric problems, reinforces the importance of providing appropriate ambulance staff training in the assessment and management of self-harm, and mental health problems more broadly, in this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 48 publications
(43 reference statements)
0
28
0
Order By: Relevance
“…32 There are, however, few studies examining self-harm after release from incarceration, which makes direct comparison between regions almost impossible. 3,4 In Australia, there is no federal correctional system, as each state or territory system operates independently. In the State of Queensland, adults are asked on reception whether they have ever selfharmed; this is combined with records from previous incarcerations and, on some occasions, information gathered informally from police, mental health records and family members.…”
mentioning
confidence: 99%
“…32 There are, however, few studies examining self-harm after release from incarceration, which makes direct comparison between regions almost impossible. 3,4 In Australia, there is no federal correctional system, as each state or territory system operates independently. In the State of Queensland, adults are asked on reception whether they have ever selfharmed; this is combined with records from previous incarcerations and, on some occasions, information gathered informally from police, mental health records and family members.…”
mentioning
confidence: 99%
“…Australian research exploring the use of tertiary health services among PWID found PWID to be frequent users of emergency department (ED) and tertiary healthcare services and that ED presentations and hospital separations were most commonly related to mental and behavioural disorders (Nambiar et al, 2018; Nambiar et al, 2017). Similarly, a study of ambulance attendances among recently released prisoners found that one in twelve attendances involved self-harm or self-harm/suicidal ideation (Borschmann, Young, et al, 2017). Another Australian study found almost half of participants presenting to ED for self-harm following release from prison were previously identified in prison health records as being at risk of self-harm (Borschmann, Thomas, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Considering mental health issues, Borschmann et al (2017) noted the need for further research on clinical management and epidemiology of reactions to self-harm, clinical outcomes and care pathways for vulnerable patients. Likewise, Cohen (36) noted the absence of behavioural risk assessment techniques and recommended that terrorism violence prevention protocols should include such.…”
Section: Discussionmentioning
confidence: 99%